Relationship between crystalline structure and mechanical behavior in isotropic and oriented polyamide 6 - Dencheva, Nadya Vasileva (2007)
Polyamide 6 (PA6) isotropic films and oriented cables were prepared by compression molding or by consecutive extrusion and cold-drawing. These samples were isothermally annealed in the 120–2008C range and were then subjected to tensile tests at room temperature. Synchrotron wide-angle X-ray scattering (WAXS) and small-angle X-ray scattering (SAXS) patterns were obtained before and after mechanical failure. These data were related with the mechanical properties of the respective PA6 samples. The annealing of isotropic PA6 resulted in an increase in the Young’s modulus (E) and yield stress (sy) values, which was attributed to the observed proportional reduction of the d-spacings of the intersheet distances in both the a-PA6 and g-PA6 polymorphs. Analysis of the WAXS and SAXS patterns of isotropic PA6 after break allowed the supposition of structural changes in the amorphous phase, with these being better pronounced with increasing annealing temperature; this made the samples less ductile. In oriented PA6 samples, annealing resulted in a drastic increase in the E and sy values accompanied by a phase transition from g-PA6 to a-PA6 and a wellpronounced reduction in the intersheet distances of both polymorphs. The stretching of the oriented samples led to an additional g-to-a transition, whose extent was also related to structural changes in the amorphous phase